2007
DOI: 10.1253/circj.71.382
|View full text |Cite
|
Sign up to set email alerts
|

Internalization and Dephosphorylation of Connexin43 in Hypertrophied Right Ventricles of Rats With Pulmonary Hypertension

Abstract: ap junctions are specialized membrane regions consisting of groups of channels that directly connect the cytoplasmic components of adjacent cells and enable intercellular communication with respect to the exchange of ions and small (<1 kDa) molecules. 1 Gap junctions are composed of transmembrane proteins that belong to the connexin family. The principal gap junctional protein expressed in ventricles of the mammalian heart is connexin43 (Cx43), although connexin40, connexin45 and connexin 30.2 (and its human o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 34 publications
1
35
1
Order By: Relevance
“…25,26,34 In human studies, downregulation of the principal gap junction protein, Cx43, was implicated in arrhythmia in ischemic heart disease and heart failure caused by DCM. 25,35 In this study, we showed that Cx43 was downregulated in H/MSod2 −/− hearts and when EUK-8 was administered to the mutant mice, the Cx43 level significantly improved without transcriptional restoration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25,26,34 In human studies, downregulation of the principal gap junction protein, Cx43, was implicated in arrhythmia in ischemic heart disease and heart failure caused by DCM. 25,35 In this study, we showed that Cx43 was downregulated in H/MSod2 −/− hearts and when EUK-8 was administered to the mutant mice, the Cx43 level significantly improved without transcriptional restoration.…”
Section: Discussionmentioning
confidence: 99%
“…Cx43 is a major gap junction protein that regulates cardiac conduction. 25,26 It is speculated that Cx43 downregulation causes the development or progression of heart failure in H/M-Sod2 −/− mice, so to test this, we investigated levels of Cx43 in H/M-Sod2 -/-mice. As shown in Figure 6, the levels of Cx43 were markedly reduced in the hearts of salinetreated H/M-Sod2 −/− mice (P<0.01).…”
Section: Euk-8 Recovers Cx43 Expression In H/m-sod2 −/− Micementioning
confidence: 99%
“…It is accepted that Cx43 undergoes trafficking from the sarcoplasmic reticulum and Golgi apparatus to GJs and endocytosis-mediated degradation in lysosomes or proteasomes. 33,34 It has also been shown that Cx43 translocates to mitochondria and affords protection in ischemic preconditioning. 26,35 The P1 fraction contained marker proteins for the sarcoplasmic reticulum, Golgi apparatus, lysosomes, and mitochondria (data not shown).…”
Section: Translocation Of Cx43 To Intercalated Disks In Brief Ischemiamentioning
confidence: 99%
“…[15][16][17] In the hypertrophied right ventricles of rats with pulmonary hypertension, Cx43 underwent internalization, dephosphorylation, and degradation. 18 In Cx43-deficient mice, GJ uncoupling induced a sharp (>80%) reduction in Cx43 expression and a moderate (~40%) decrease in CV, 19,20 as well as regional heterogeneity in repolarization current. 21 This mutation resulted in high (~80%) mortality due to spontaneous arrhythmias in 1 study, 19 whereas other groups have documented inducible arrhythmias in the same model.…”
mentioning
confidence: 94%